2019
DOI: 10.1111/avsc.12443
|View full text |Cite
|
Sign up to set email alerts
|

Elymus athericus encroachment in Wadden Sea salt marshes is driven by surface elevation change

Abstract: Questions What are the main drivers of vegetation succession and the encroachment of Elymus athericus (Link) Kerguélen in ungrazed Wadden Sea salt marshes? Is (a) elevation, a proxy for tidal inundation and thus abiotic conditions, limiting the expanse of Elymus. Does sedimentation increase the spread of Elymus by (b) leading to surface elevation change or does it (c) add nitrogen and thereby allows Elymus to grow in lower elevation? Location Salt marsh at Sönke‐Nissen‐Koog, Wadden Sea National Park Schleswig‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…For instance, nitrogen is often the limiting soil nutrients restraining plant growth in saline environments [ 74 ], as plants also use nitrogen to increase salt tolerance by synthetizing nitrogen compounds [ 14 ]. In this context, interaction with microbes could contribute to nitrogen acquisition, as demonstrated by the higher abundance of taxa with the potential ability to fix atmospheric nitrogen in the endosphere of ecotypes from HE, which showed lower soil nitrogen content, especially in 53-year-old sites [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nitrogen is often the limiting soil nutrients restraining plant growth in saline environments [ 74 ], as plants also use nitrogen to increase salt tolerance by synthetizing nitrogen compounds [ 14 ]. In this context, interaction with microbes could contribute to nitrogen acquisition, as demonstrated by the higher abundance of taxa with the potential ability to fix atmospheric nitrogen in the endosphere of ecotypes from HE, which showed lower soil nitrogen content, especially in 53-year-old sites [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a typical species of the high saltmarsh. Its establishment is facilitated by natural sedimentation processes (Nolte et al 2019 ). It was observed that E .…”
Section: Introductionmentioning
confidence: 99%
“…athericus is able to partially invade the low marsh overgrowing smaller species (Bakker et al 2009 ). When grazing is abandoned or reduced, the species becomes dominant (Nolte et al 2019 , Bakker et al 2020 ) and then negatively affects species diversity of plants (Wanner et al 2014 ) or halophilic spiders (Pétillon et al 2005 ) and reduces the habitat suitability for certain breeding birds (Mandema et al 2015 ). Nevertheless, long-term abandoned saltmarshes with high dominance of E .…”
Section: Introductionmentioning
confidence: 99%
“…Encroachments of new species into ecosystems, which lead to dramatic changes in vegetation composition, might have significant consequences for ecosystem functions (Hibbard et al, 2001;Archer et al, 2017;Nolte et al, 2019). In particular, new species encroachments might affect the quality and quantity of primary and secondary production, decomposition and nutrient cycling, and the pools and flows of materials (Eldridge et al, 2011;Friedrich et al, 2011;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…nitrogen fixation by Myrica faya changing the nutrient status of entire islands on Hawaii (Vitousek, 1990). The consequences of new species encroachments have been widely described in many kinds of terrestrial ecosystems (Schlesinger et al, 1990;McLaren et al, 2017;Zhou et al, 2018), mainly focusing on woody plant species (Hibbard et al, 2001), but the consequences of non-woody-plant species encroachments have seldom been tested especially in coastal wetlands (but see Nolte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%